2017
DOI: 10.1149/2.0551713jes
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Induced Self-Modification of Cermet Anodes of Ni–CeO2-Based Oxide for Solid Oxide Fuel Cells

Abstract: Recently, the strong chemical interaction between Ni and GDC (Gd 2 O 3 −CeO 2 ) was reported for the cermet anode of Ni−GDC in solid oxide fuel cells (SOFCs); 1 CeO 2 species migrated on the Ni surface after exposure to the reducing atmosphere. This surface modification of nickel affected the catalytic properties for carbon deposition and CO adsorption. Generally, such a chemical interaction is promoted by the oxidation-reduction (redox) treatment. In this study, then, the influence of redox treatment on catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…ALD is ideal for coating the Ni phase with a thin overcoat to suppress the agglomeration and oxidation of the underlying Ni [111]. A similar approach would seem to be ideal for depositing ceria to prevent carbon formation [112].…”
Section: Modification Of Sofc Anodesmentioning
confidence: 99%
“…ALD is ideal for coating the Ni phase with a thin overcoat to suppress the agglomeration and oxidation of the underlying Ni [111]. A similar approach would seem to be ideal for depositing ceria to prevent carbon formation [112].…”
Section: Modification Of Sofc Anodesmentioning
confidence: 99%
“…Furthermore, the FIB-SEM investigation identified the accelerated coarsening of Ni in contact with the GDC as one possible reason for electrolyte delamination. Several authors [35,45] have reported stronger Ni coarsening in the presence of the GDC due to strong interfacial interaction. This must also be considered during the processing of Ni/GDC anodes [13].…”
Section: 3mentioning
confidence: 99%
“…These effects lead to increased tortuosity of the Ni and YSZ, while the tortuosity of the pores decreases. The redox behavior of Ni/GDC anodes has been less reported in the literature so far [15,35,36]. GDC is an attractive material for the ceramic backbone of SOFCs, since it contributes to the electrochemical performance of the anode.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations